The use of telehealth in the approach to Chronic Non-Communicable Diseases in times of a pandemic by Covid-19: an integrative review (Research, Society and Development, 2022)
The present study aims to analyze scientific evidence about the relevance of the practice of telehealth in the care of individuals in a chronic situation in the time of a pandemic caused by COVID-19. This is an integrative review of the literature that focuses on the realization of a synthesis of articles and the combination of them on the researched topic; for the bibliographic survey, the flowchart guided by (PRISMA) was used, which resulted in a total of 7 articles for analysis and discussion. To carry out this search, the Descriptors in Health Sciences (DeCS) and Medical Subjectc Headings (MeSH) and Keywords: Non-Communicable Diseases, Telemedicine and COVID-19, and their respective English correspondents grouped by the Boolean operator “AND” were used. and “OR”, for the keywords. Thus, when analyzing the articles obtained from the present research, it was possible to identify studies that address the impacts on care for patients with NCDs in times of social isolation and their reordering in care with the use of telehealth as a tool for this specific population. It is necessary to develop educational programs that provide users with greater knowledge about the use of these technologies, aiming at the adhesion and expansion of this system in order to facilitate its effectiveness in the care of individuals in a situation of chronicity.